Effectiveness of government regulation number 35 of 2021 and company regulations on granting sanctions letters to workers at pt X - Ayu Aulia Rahmitasari; Siti Hajati Hoesin (Trigin Publisher, 2023)
Manpower laws and regulations regarding the granting of sanctions letters to workers at PT. X that violates the provisions in the company regulations and/or employment agreement has not been fully implemented. Given the violation committed by the company by providing sanctions letters in the form of warning letters that are not consecutive to workers. Using non-doctrinal or empirical research methods, the main data sources used are secondary data supported by primary data from interviews with several informants and primary legal materials consisting of laws and regulations (Law No. 13 of 2003 concerning Manpower, Perpu No. 2 of 2022 concerning Job Creation, and PP No. 35 of 2021 concerning PKWT, Outsourcing, Rest Time, and Working Time, and Layoffs). This type of research is doctrinal or juridical normative. The nature of this research is qualitative research. So this paper will analyze how effective PP No. 35 of 2021 and Company Regulations are on granting sanctions letters to workers at PT. X and the factors that play a role in the effectiveness of the rule.